Knowledge and Attitude Towards Eye Donation among Young Adults in Sainamaina Municipality - Rana, Susma; Poudel, Shrijana (International Research Journal of MMC, 2025)
Corneal transplantation is a very successful treatment for corneal blindness. However, the main problem is the lack of donor tissue. Young adults represent a potential donor pool. So, assessing their knowledge and attitude helps to aid in crafting targeted educational campaigns potentially increasing the number of future donors. This study is to assess the level of knowledge and attitude on eye donation among young adults in a ward of Sainamaina Municipality. A descriptive cross-sectional study conducted among young adults of age between 19 to 40 years in Sainamaina Municipality. Non-probability purposive sampling technique was used to collect data by interviewing the individual by using structured interview schedule. The collected data were entered, organized and coded in Statistical Package for Social Science (SPSS) and analyzed by using descriptive and inferential statistics. Out of 119 respondents, 46.2 percent belonged to the 30-39 age group with the mean age of 29 ± 6.38. Regarding the level of knowledge about eye donation, more than half of the respondents (54.6%) had a low level of knowledge and 45.4 percent had moderate level of knowledge. But 60.5 percent respondents had positive attitude toward eye donation and 39.5 percent had negative attitude. In terms of willingness to donate eye, only 21.8 percent of the respondents were willing to donate their eyes. The study highlighted that though respondents had positive attitude towards eye donation, they had poor knowledge and low willingness to donate their eyes. So, different educational campaigns, interactive workshops on eye donation to enhance their knowledge and in-depth qualitative studies are necessary to identify the reasons behind the discrepancy between attitude and willingness of public on eye donation seems necessary. This study might help to enhance knowledge of eye donation in the community.